Edward Jenner : conqueror of smallpox - Taylor, Boswell (London : Macmillan & Co. LTD, 1960)
A biography of the British physician who discovered vaccination as a means of preventing smallpox.
Includes bibliography.
Keywords: Jenner, Edward, -- 1749-1823 -- Juvenile literature; Jenner, Edward, -- 1749-1823.; Physicians -- England -- Biography -- Juvenile literature; Smallpox -- Vaccination -- History -- Juvenile literature; Physicians